Modelling and design of a synchronous homopolar machine for aircraft DC power generation - Vannini, Amedeo (2025)
Driven by stringent regulations and the net-zero emission target essential for limiting global temperature rise and mitigating the effects of climate change, the aerospace industry views aircraft electrification as a potential solution for sustaining its business. The More-Electric Aircraft concept is gradually advancing towards hybrid and turbo-electric drivetrain configurations with DC primary power distribution, serving as an intermediate step towards fully electrified aircraft. In this context, onboard electric power generation has to satisfy increased propulsive power demands, reaching the multi-megawatt scale, while maintaining strict aerospace standards for reliability, power density, and efficiency. Independent power generation and propulsion channels are often implemented to ensure sufficient redundancy and reliability. However, when using permanent magnet synchronous generators, full-rated active power electronic converters are necessary, often introducing complexity, cost, and potential reliability concerns in multi-phase and redundant architectures. Solutions based on front-end diode rectifiers represent valid alternatives thanks to their simplicity, cost-effectiveness, compactness, and higher efficiency. In this scenario, synchronous homopolar machines present a compelling option as a robust electro-mechanical conversion system, characterised by their stationary DC excitation and simple rotor design- free from permanent magnets and brush-slip systems- enabling high-speed operation. The controllable excitation field provides full voltage-control capability, reliable de-excitation, and ease of integration with advanced thermal management systems or superconductive technologies. Despite these advantages, their diffusion is hindered by their complex three-dimensional magnetic behaviour which requires time-consuming 3D finite-element analysis for performance prediction, limiting its utilisation in the design optimisation process. While analytical methods offer a favourable trade-off between accuracy and computational burden, a significant gap in the literature remains regarding the electromagnetic modelling and design of this machine topology. This thesis proposes a novel generation unit concept based on synchronous homopolar generators with a dual DC-link configuration, where each power bus is supplied through two series-connected rectifiers and a direct oil-cooled excitation coil provides the DC-link voltage regulation. The manuscript tackles the challenges of sizing and analytically modelling this machine topology, filling the existing gap in the literature. The developed analytical tools are incorporated into a genetic design optimisation algorithm to determine the optimal set of input parameters. The design, prototyping, and testing of a proof-of-concept generation unit delivering 1.2kW at 6000rpm are detailed, with the ultimate goal of validating the proposed modelling and design approaches through a comprehensive electromagnetic and thermal testing campaign. Although the design exercise and experimental validation are performed on a small-scale prototype, this work may provide a foundation for designing an active power electronic-free electric generation unit for future aerospace electric power generation.